Method for preparing lithium iron phosphate from copper slag
By optimizing the roasting and leaching process, combined with the precipitation of sodium fluoride and the use of diammonium hydrogen phosphate solution, the problems of separation difficulties and impurities in the copper slag were solved, and lithium iron phosphate materials with excellent electrochemical properties were prepared, achieving efficient resource utilization of copper slag.
Patent Information
- Application Number
- CN202411592845.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, the process of preparing lithium iron phosphate using copper slag has problems such as difficulty in separation of iron and silicone and great influence on impurities such as Al and Mg.
By optimizing the calcination temperature and time, efficient leaching of iron and enriching silicon, introducing sodium fluoride precipitant to remove impurities, using diammonium hydrogen phosphate solution as the phosphorus source and pH regulator, and finally preparing lithium iron phosphate through ball milling and roasting steps.
It realizes efficient resource utilization of iron in copper slag, improves the electrochemical performance of lithium iron phosphate, reduces environmental pollution, and saves costs.
Smart Images

Figure CN119528100A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials, and in particular to a method for preparing lithium iron phosphate by utilizing copper slag. Background Art
[0002] Copper slag is a by-product of the copper smelting process. Currently, the global annual copper slag production exceeds 40 million tons. Due to the large amount of heavy metals contained in it, it is considered a solid waste with potential risks to the environment. At present, the main treatment method for copper slag is on-site storage, which accounts for more than 80% of copper slag. A small part of copper slag is used as an additive in cement production. Copper slag also contains a large amount of iron, mainly in the form of olivine and magnetite, which provides ideas for the resource utilization of copper slag.
[0003] The rapid development of electric vehicles and grid energy storage has continuously increased the requirements for lithium-ion battery cathode materials. Lithium iron phosphate cathode materials are widely used in the field of energy storage due to their superior structural stability and low cost. As a precursor of lithium iron phosphate cathode materials, iron phosphate has good thermal stability and durability, and its preparation technology has also made great progress in the past period of time. However, the activity, structure and composition of iron phosphate have a significant impact on the performance of lithium iron phosphate cathode materials. Therefore, the preparation of iron phosphate with excellent performance is very critical for subsequent battery manufacturing.
[0004] Chinese invention patent 202410633536.0 discloses "a method for preparing iron phosphate from laterite nickel ore and phosphate ore in a short process". This method crushes and mixes laterite nickel ore and phosphate ore, dissolves them with nitric acid, obtains acid leaching solution for hydrothermal reaction, and obtains crude iron phosphate dihydrate and mother liquor; crude iron phosphate dihydrate is added to phosphoric acid aqueous solution for washing and aging treatment to obtain high-purity iron phosphate dihydrate and washing water, and then elemental iron is added to the mother liquor for deep dephosphorization to obtain dephosphorized liquid and ferrophosphorus slag, which is reused as a phosphorus source, and the dephosphorized liquid is subjected to step precipitation separation to obtain by-products and pure magnesium nitrate solution, and subsequently magnesium oxide products and nitric acid are obtained. This method is efficient and simple, has the advantages of low cost, green and low-carbon environmental protection, and is conducive to large-scale industrial production and promotion.
[0005] Chinese invention patent 202410368764.X discloses "a method for preparing lithium iron phosphate using ferrophosphorus slag and its use". This method dehydrates and decarbonizes the ferrophosphorus slag, then compounds it with battery-grade iron phosphate, and reacts it with the raw lithium source and carbon source to generate lithium iron phosphate. This method can not only make full use of the phosphorus and iron elements in the ferrophosphorus slag, but also introduce the beneficial impurity element titanium as a doping element.
[0006] Chinese invention patent 202311274371.4 discloses a method for preparing battery-grade iron phosphate dihydrate using flotation copper tailings, which heats the flotation copper tailings and mixes them with acid, stirs until the acid solution evaporates, then adds distilled water for stirring and solid-liquid separation, oxidizes the divalent iron in the resulting iron-zinc solution into trivalent iron; adds anhydrous disodium hydrogen phosphate solid or dodecahydrate disodium hydrogen phosphate solid to obtain crude iron phosphate, and then recrystallizes and removes impurities from the crude iron phosphate to obtain battery-grade iron phosphate dihydrate. This method achieves efficient separation of iron and silicon in flotation copper slag and realizes high-value utilization.
[0007] The present invention provides a new method for preparing lithium iron phosphate using copper slag. In view of the problems of difficulty in separating iron from silicon and great influence of impurity elements such as Al and Mg in the current process of preparing lithium iron phosphate using copper slag, this scheme is based on the optimization of the pre-treatment process to achieve efficient leaching of iron and is conducive to the enrichment of silicon. The method of introducing a sodium fluoride precipitant to remove impurities by precipitation not only achieves the purification of the iron-containing leachate, but also achieves the separation and enrichment of valuable metals, which is conducive to the multi-faceted resource utilization of copper slag. As an alkaline phosphorus source, diammonium hydrogen phosphate solution not only provides a phosphorus source for iron phosphate precipitation, but also serves as a pH regulator for the system, saving the cost of ammonia water. In addition, the lithium iron phosphate material obtained by this scheme has better electrochemical properties than other lithium iron phosphates prepared using copper slag. This method provides a simple and efficient method for the resource utilization of copper slag, which helps to provide guidance for the resource utilization of other silicon-rich iron minerals and solid wastes. Summary of the invention
[0008] The purpose of the present invention is to provide a method for preparing lithium iron phosphate using copper slag. The lithium iron phosphate obtained by this method has good electrochemical properties. At the same time, the separation of by-products in the process realizes the separation and enrichment of silicon, zinc, aluminum, magnesium and lead, which is beneficial to their resource utilization.
[0009] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:
[0010] A method for preparing lithium iron phosphate using copper slag comprises the following steps:
[0011] S1: roasting the copper slag in air atmosphere for 20-60 minutes;
[0012] S2: Mix the calcined copper slag with sodium hydroxide solution and heat for 3 hours before solid-liquid separation;
[0013] S3: adding hydrochloric acid solution to the alkali leaching residue, heating and stirring for a period of time, filtering while hot to obtain acid leaching solution and acid leaching residue;
[0014] S4: Add Al to the acid leaching solution 3+ , Ca 2+and Mg 2+ 1-2.5 times the theoretical mass of the precipitated sodium fluoride is stirred for reaction for 0.5-2.5 hours; after filtering, a purified acid leaching solution and a filter residue are obtained, and the filter residue is dried and collected and stored;
[0015] S5: adding diammonium hydrogen phosphate solution to the acid leaching solution, adjusting the pH under heating conditions, reacting for 1 hour, heating and aging, filtering, washing, and drying to obtain ferric phosphate dihydrate;
[0016] S6: heating the obtained dihydrated ferric phosphate in air to dehydrate it, thereby obtaining anhydrous ferric phosphate;
[0017] S7: after mixing anhydrous ferric phosphate, lithium carbonate and glucose, ball milling is performed for a period of time using ethanol as a dispersant, and then the slurry is dried and the ball material is separated;
[0018] S8: After grinding the dry material, calcining it in an argon atmosphere to obtain a lithium iron phosphate positive electrode material. Furthermore, the calcination temperature of the copper slag in step S1 is 800-1000°C, and the calcination time is 20-60min;
[0019] Furthermore, in step S2, the process temperature is 110° C., the stirring rate is 130 rpm, the concentration of the sodium hydroxide solution is 160 g / L, the reaction liquid-solid ratio is 5:1, and the reaction time is 3 h.
[0020] Furthermore, in step S3, the process temperature is 75-95° C., the stirring rate is 100-120 rpm, the concentration of the hydrochloric acid solution is 2 M, the reaction liquid-solid ratio is 8-12:1, and the reaction time is 1-3 h.
[0021] Furthermore, in step S4, the amount of sodium fluoride added is 1-2.5 times the sum of the theoretical mass of sodium fluoride required for Al, Mg and Ca fluorides in the acid leaching solution, the stirring rate is 400 rpm, and the reaction time is 0.5-1.5 h.
[0022] Furthermore, in step S5, the amount of diammonium hydrogen phosphate added is calculated according to P:Fe=1.10-1.25, the reaction temperature is 65°C, the reaction time is 60 minutes, the aging temperature is 90°C, the aging time is 5 hours, the drying temperature is 80°C, and the drying time is 10 hours.
[0023] Furthermore, the heating time of step S6 is 3 hours and the heating temperature is 650°C.
[0024] Furthermore, the molar mass ratio of iron phosphate to lithium carbonate in step S7 is 2:1, the amount of glucose added is 20% of the theoretical mass of lithium iron phosphate, the mass ratio of zirconium oxide balls to material is 10:1, ethanol is added to submerge the ball material, the planetary ball mill speed is 700 rpm, the ball milling time is 4 hours, and the slurry drying temperature is 70°C.
[0025] Furthermore, the sintering temperature of step S8 is 700° C., the sintering time is 10 h, and the argon gas flow rate is 300 ml / min.
[0026] Further, the preparation principle of the present invention is as follows:
[0027] During the roasting process, the copper slag mainly undergoes the following chemical reactions:
[0028] 2Fe2SiO4+O2→2Fe2O3+2SiO2
[0029] During the alkaline leaching process, the copper slag mainly undergoes the following chemical reactions:
[0030] SiO2+2NaOH→Na2SiO3+H2O
[0031] Al2O3+2NaOH=Na2Al2O4+H2O
[0032] The following chemical reactions occur during the pickling process:
[0033] Fe2O3+6HCl→2FeCl3+3H2O
[0034] The reactions that occur during the impurity removal process are mainly as follows:
[0035] Al 3+ +3F-→AlF3
[0036] Mg 2+ +2F-→MgF2
[0037] Ca 2+ +2F-→CaF2
[0038] The main reactions during the Chen Tie process are as follows:
[0039] Fe 3+ +PO4 3- →FePO4
[0040] The main chemical reactions in the synthesis process of lithium iron phosphate are:
[0041] 12Li2CO3+24FePO4+C6H 12 O6→24LiFePO4+6H2O+18CO2
[0042] Beneficial effects of the present invention:
[0043] The present invention uses copper slag to prepare lithium iron phosphate positive electrode materials, converts the iron in the copper slag into products with high added value, realizes efficient resource utilization of copper slag, and reduces the environmental burden. Copper slag is not only rich in iron, but also contains other heavy metals and valuable metals such as zinc, aluminum, magnesium, etc. By optimizing the roasting temperature (800-1000°C) and time (20-60 minutes), the silicates and oxides in the copper slag are converted into soluble forms, especially Fe2SiO4 is converted into Fe2O3 and SiO2, which promotes the subsequent leaching process. In the alkaline leaching step, the strong alkalinity of sodium hydroxide can effectively react SiO2 with NaOH to generate Na2SiO3, thereby enriching the iron element into the leachate. This process not only improves the leaching rate of iron, but also converts the copper slag, which was originally an environmental hazard, into a reusable raw material, achieving the dual effects of environmental protection and resource conservation.
[0044] In order to solve the problem that the binding effect of olivine on iron and other valuable metals in copper slag increases the difficulty of resource utilization of copper slag, the present invention adopts a pyrometallurgical-wet method combined treatment, and oxidative roasting is used to oxidize and decompose the iron olivine into iron oxide and silicon dioxide, which greatly reduces the difficulty of iron leaching. Other elements enter the liquid phase during the leaching process for enrichment. The main chemical reactions in this process are as follows:
[0045] 2Fe2SiO4+O2→2Fe2O3+2SiO2
[0046] The presence of silicon dioxide makes the filtration process of acid leaching and iron phosphate precipitation more difficult, and also affects the quality of iron phosphate. This method removes amorphous silicon dioxide that affects the subsequent process through alkaline leaching. At the same time, sodium hydroxide can also partially remove the impurity element Al that has a greater impact on lithium iron phosphate. The chemical reactions in this process are as follows:
[0047] SiO2+2NaOH→Na2SiO3+H2O
[0048] Al2O3+2NaOH=Na2Al2O4+H2O
[0049] The copper slag after roasting mainly exists in the form of Fe2O3, and high temperature roasting may form an acid-resistant oxide film on the surface of mineral particles, thus affecting the leaching efficiency. - The presence of can corrode the oxide film, so that the hematite phase is directly in contact with hydrochloric acid, making Fe 3+ Leaching to liquid phase. The main reactions are as follows:
[0050] Fe2O3+6HCl→2FeCl3+3H2O
[0051] Impurity ions represented by Al enter the liquid phase during the acid leaching process, and due to the close precipitation area, some impurity ions will precipitate during the precipitation process, thus affecting the product quality. The introduction of sodium fluoride can achieve the precipitation and removal of some impurity ions in the acid leaching solution, which is beneficial to the purity of the subsequent synthetic iron phosphate precipitation. The Ksp of the three fluorides at room temperature is as follows:
[0052] Species Ksp <![CDATA[AlF3]]> <![CDATA[1.6*10 -33 ]]> <![CDATA[MgF2]]> <![CDATA[6.4*10 -9 ]]> <![CDATA[CaF2]]> <![CDATA[3.95*10 -11 ]]> <![CDATA[PbF2]]> <![CDATA[3.7*10 -8 ]]> <![CDATA[FeF3]]> 5.63
[0053] The main reaction equation for impurity removal is as follows:
[0054] Al 3+ +3F - →AlF3
[0055] Mg 2+ +2F - →MgF2
[0056] Ca 2+ +2F - →CaF2
[0057] By properly controlling the acid leaching conditions, when synthesizing iron phosphate, the addition of diammonium hydrogen phosphate solution not only provides raw materials for the synthesis of iron phosphate, but also serves as a pH regulator for the reaction system. By changing the pH value of the solution, the behavior of impurities can be precisely controlled, so that the entire process does not require the addition of ammonia water or sodium hydroxide. Dehydration of dihydrate iron phosphate at 650°C obtains α-spinel iron phosphate, which improves its electrochemical stability. The main chemical reactions that occur during the precipitation process are as follows:
[0058] Fe 3+ +PO4 3- →FePO4
[0059] The design is based on the molar ratio of P:Fe (1.10-1.25) to ensure the formation of iron phosphate (FePO4). Under heating conditions, precise control of the reaction time (such as aging for 5 hours after 60 minutes of reaction at 65°C) not only facilitates the interaction during the synthesis process, but also ensures that the generated dihydrate iron phosphate is converted into anhydrous iron phosphate after drying, thereby providing a more ideal precursor for the subsequent lithiation reaction. In the lithiation reaction, anhydrous iron phosphate, lithium carbonate and glucose interact to eventually form LiFePO4. The optimization of this reaction gives the final product excellent structural stability and electrochemical properties, which is suitable for efficient lithium-ion battery applications.
[0060] The preparation process of the present invention is simple in design, simple in operation, and convenient for industrial large-scale production. Compared with the existing technologies such as strong acid evaporation treatment, the present method realizes the separation of iron and silicon through oxidative roasting while also promoting the oxidation of iron, saving the cost of using hydrogen peroxide. Alkali leaching avoids the influence of silicic acid on the solid-liquid separation in the acid leaching and precipitation process, and also obtains a leachate with a high silicon content, which is conducive to further purification and utilization. At the same time, part of Al reacts with the alkali in this process and enters the liquid phase, reducing the amount of subsequent sodium fluoride impurity removal. The introduction of sodium fluoride in the impurity removal process allows valuable metals such as Al and Mg to be separated in the form of precipitation, which is conducive to the subsequent purification and utilization of by-products. According to the potential-pH of the iron phosphate precipitation, the present method selects a precipitation method with simple operation difficulty and low product impurities to prepare iron phosphate from the copper slag leachate. At the same time, practice has proved that the iron phosphate product obtained under the conditions of 1.5 pH and 65 ° C has a small particle size and good crystallinity, and under this condition, the Fe in the acid leaching solution is almost converted into iron phosphate precipitation, with high utilization rate.
[0061] In the process of synthesizing iron phosphate, the present invention uses ethanol as a dispersant to high-speed ball-mill materials such as iron phosphate and lithium carbonate, so that the materials are evenly mixed and the particle size of iron phosphate is appropriately reduced, thereby creating a shorter path for ion migration in the subsequent battery charging and discharging process, so that lithium iron phosphate has better electrochemical performance.
[0062] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0064] Figure 1 This is the XRD pattern of the original copper smelting slag;
[0065] Figure 2 Process flow chart of the present invention;
[0066] Figure 3 This is the XRD diagram of the calcined copper slag obtained in Example 1 of the present invention;
[0067] Figure 4 This is the XRD pattern of ferric phosphate dihydrate obtained in Example 1 of the present invention;
[0068] Figure 5 This is a SEM image of ferric phosphate dihydrate obtained in Example 1 of the present invention;
[0069] Figure 6This is the XRD pattern of anhydrous ferric phosphate obtained in Example 1 of the present invention;
[0070] Figure 7 This is a SEM image of the anhydrous ferric phosphate obtained in Example 1 of the present invention;
[0071] Figure 8 This is the XRD diagram of the lithium iron phosphate obtained in Example 1 of the present invention;
[0072] Fig. 9 This is a SEM image of the lithium iron phosphate obtained in Example 1 of the present invention;
[0073] Fig.10 This is a cycle performance diagram of lithium iron phosphate obtained in Example 1 of the present invention;
[0074] Fig.11 This is a rate performance diagram of lithium iron phosphate obtained in Example 1 of the present invention;
[0075] Fig.12 This is the XRD diagram of the calcined copper slag obtained in Example 2 of the present invention;
[0076] Fig.13 This is the XRD diagram of the calcined copper slag obtained in Example 3 of the present invention. DETAILED DESCRIPTION
[0077] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0078] The copper smelting slag used in the examples was provided by a company in Sichuan, and its phase composition is as follows: Figure 1 As shown, the main elements and their contents are shown in Table 1. The total iron content in the copper slag is 309.212g / Kg. In addition to iron, the Al content is relatively high among the main metal elements in the copper smelting slag, and it mainly exists in the form of silicates. Because the formation conditions of its phosphate compound are similar to those of FePO4, it is easy to generate AlPO4 and exist in FePO4 as an impurity, affecting the purity and performance of the product. Therefore, efficient separation of Fe and Al is one of the technical challenges for synthesizing LiFePO4 from copper slag. In response to this problem, the impurity removal process of this scheme converts Al into AlF3 precipitation and removes it from the acid leaching solution. This method can also simultaneously remove Mg and Ca in the acid leaching solution to achieve the separation of some impurities. At the same time, Si, as the main component, is the main element that forms olivine. Through oxidative roasting, olivine is decomposed into amorphous silica, and then alkali leaching is used to achieve the purpose of removing silicon.
[0079] Table 1
[0080]
[0081] Example 1
[0082] like Figure 2 As shown, a method for preparing lithium iron phosphate using copper slag described in this embodiment includes the following steps:
[0083] S1: Weigh 15g of copper slag in a corundum crucible and place it in a muffle furnace. Heat it to 900℃ at 10℃ / min, keep it warm for 40min, and cool it to room temperature for later use. The XRD pattern of the calcined copper slag is as follows: Figure 3 As shown, compared with the original copper slag, the fayalite phase in the copper slag disappeared after roasting, and the main phase was transformed into the hematite phase, which indicated the decomposition of fayalite and the successful oxidation of iron.
[0084] S2: Take the copper slag from step S1, add 160 g / L NaOH solution at a liquid-to-solid ratio of 5:1, heat and stir, the leaching temperature is 110°C, the stirring rate is 130 rpm, the reaction time is 3 h, and after solid-liquid separation, a silicon-rich solution and alkaline leaching residue are obtained. The main elements of the alkaline leaching solution and the alkaline leaching residue are shown in Table 2.
[0085] Table 2
[0086] element Fe Al Zn Mg Si Ca Alkali leaching solution (mg / L) 109.01 1014.87 69 141.45 26982.60 273.66 Alkaline leaching residue (%) 39.63% 2.34 2.54 1.15 1.48% 3.01 Acid leaching solution (mg / L) 36327.5 2261.16 2381.25 621.02 591.47 3041.35 Purification liquid (mg / L) 35946.14 126.3 2336 88.75 568.01 402.62
[0087] S3: Take the alkaline leaching residue in step S2, add a 2M hydrochloric acid solution at a liquid-to-solid ratio of 10:1 and heat and stir. The leaching temperature is 85°C, and the reaction is stirred at 150rpm for 2h. Filter while hot to obtain an acid leaching solution and a filter residue. The element content of the acid leaching solution is shown in Table 2. Through alkaline leaching, Si in the copper slag is leached into the leaching solution in large quantities, with a good silicon removal effect, and part of Al is also leached in the process.
[0088] S4: NaF was added to the acid leaching solution at a mass of 1.5 times the theoretical NaF mass of AlF3, MgF2, and CaF2 as products, and stirred at 200 rpm for 1 hour at room temperature. The solid and liquid were separated, and the purified liquid and impurities were precipitated. The elemental composition of the purified liquid is shown in Table 2. After purification, a large amount of Al, Mg, and Ca in the liquid were removed.
[0089] S5: Add diammonium hydrogen phosphate solution to the purified solution in step S4 at a stirring speed of 400 rpm with a P:Fe ratio of 1.20, and adjust the pH to 1.5. The reaction time is 1 hour, and then the temperature is raised to 90°C for aging for 5 hours. Immediately after the reaction, the solution is filtered and washed with hot water for 3 times. The filter residue is placed in a 100°C forced air drying oven to dry to obtain dihydrated iron phosphate, the XRD and SEM images of which are shown in FIG. Figure 4 , 5XRD shows that the dihydrated iron phosphate obtained by this method conforms to the standard PDF card of dihydrated iron phosphate; SEM images and EDS energy spectrum preliminarily prove that the obtained substance is a flocculent iron phosphide compound with a relatively uniform particle size, and its particle size is within 5μm.
[0090] S6: Sinter the dihydrated iron phosphate obtained in step S5 at 650°C in air atmosphere for 3 hours, and grind to obtain anhydrous iron phosphate. Figure 6 , 7 XRD shows that the iron phosphate obtained under this condition has a good crystalline state; SEM images and EDS spectra also prove that the obtained substance is a phosphorus iron compound, and its morphology is flocculent, and the three elements P, Fe, and O are evenly distributed in the product.
[0091] S7: The anhydrous iron phosphate obtained in step S6 is mixed with the molar mass ratio of iron phosphate to lithium carbonate of 2:1, the amount of glucose added is 20% of the theoretical mass of lithium iron phosphate, and the mass ratio of zirconium oxide balls to the material is 10:1, and then anhydrous ethanol is added to submerge the balls, and the material is ground in a planetary ball mill for 4 hours at a speed of 700 rpm. Then the balls are separated and the mixture is dried at 70°C for 10 hours.
[0092] S8: Place the dry material obtained in step S7 in a corundum crucible, and calcine it in a tube furnace for 10 hours with nitrogen as protective gas, the calcination temperature is 700°C, and the air flow rate is controlled at 300ml / min. The XRD and SEM images of the obtained lithium iron phosphate are as follows: Figure 8 , 9 As shown. The XRD graph shows that the obtained product meets the standard PDF card of LiFePO4, and there is a carbon peak in the phase, which confirms the coating effect of carbon on its surface to a certain extent, improving the conductivity of the product. The SEM graph shows that the obtained product has a fine and uniform particle size distribution, and the particle size of the primary particles reaches the submicron level. Its element content is shown in Table 3. The cycle performance and rate performance of the obtained lithium iron phosphate positive electrode material are shown in Fig.10 , 11 As shown in Figure 2, the first cycle discharge capacity of lithium iron phosphate obtained by this method at 1C reaches 142.1 mAh g -1 After 200 cycles, the capacity retention rate is still above 96%. The lithium iron phosphate has good rate performance, with a capacity of 55 mAh g at 5C rate. -1 The discharge specific capacity and the good recovery force after cycling at high rates indicate the stability of its structure.
[0093] Table 3
[0094] element% Li Fe P Al Mg Ca Example 1 5.12 37.8 22.1 0.02 0.005 0.005 Example 2 5.21 38.4 21.7 0.09 0.01 0.01 Example 3 5.09 37.5 22.4 0.02 0.005 0.005
[0095] Example 2
[0096] A method for preparing lithium iron phosphate using copper slag described in this embodiment comprises the following steps:
[0097] S1: Weigh 15g of copper slag in a corundum crucible and place it in a muffle furnace. Heat it to 800℃ at 10℃ / min, keep it warm for 20min, and cool it to room temperature for later use. The XRD pattern of the calcined copper slag is as follows: Fig.12 As shown, compared with the original copper slag, the main phase of the copper slag after roasting is transformed into hematite phase, but fayalite still exists, indicating incomplete oxidation of the copper slag at this temperature.
[0098] S2: Take the copper slag from step S1, add 160 g / L NaOH solution at a liquid-to-solid ratio of 5:1, heat and stir, the leaching temperature is 110°C, the stirring rate is 130 rpm, the reaction time is 3 h, and after solid-liquid separation, a silicon-rich solution and alkaline leaching residue are obtained.
[0099] S3: Take the alkaline leaching residue from step S2, add 2M hydrochloric acid solution at a liquid-to-solid ratio of 8:1 and heat with stirring. The leaching temperature is 75°C, and the reaction is stirred at 150 rpm for 1 hour. Filter while hot to obtain an acid leaching solution and a filter residue.
[0100] S4: Add NaF to the acid leaching solution at 1.0 times the theoretical NaF mass of AlF3, MgF2, and CaF2 as products, stir at 200 rpm for 0.5 h at room temperature, separate the solid and liquid, and precipitate the purified liquid and impurities.
[0101] S5: Add diammonium hydrogen phosphate solution to the purified solution in step S4 at a stirring speed of 400 rpm with a P:Fe ratio of 1.15, and adjust the pH to 1.5. The reaction time is 1 hour, and then the temperature is raised to 90°C for aging for 5 hours. Immediately after the reaction, the solution is filtered and washed with hot water for 3 times. The filter residue is placed in a 100°C forced air drying oven for drying to obtain dihydrated iron phosphate.
[0102] S6: Sinter the dihydrate iron phosphate obtained in step S5 at 650° C. in an air atmosphere for 3 h, and grind to obtain anhydrous iron phosphate
[0103] S7: The anhydrous iron phosphate obtained in step S6 is mixed with the molar mass ratio of iron phosphate to lithium carbonate of 2:1, the amount of glucose added is 20% of the theoretical mass of lithium iron phosphate, and the mass ratio of zirconium oxide balls to the material is 10:1, and then anhydrous ethanol is added to submerge the balls, and the material is ground in a planetary ball mill for 4 hours at a speed of 700. Then the balls are separated and the mixture is dried at 70°C for 10 hours.
[0104] S8: The dry material obtained in step S7 is placed in a corundum crucible, and calcined in a tube furnace for 10 hours with nitrogen as protective gas, the calcination temperature is 700° C., and the air flow rate is controlled to be 300 ml / min. The element composition of the obtained lithium iron phosphate is shown in Table 3.
[0105] Example 3
[0106] A method for preparing lithium iron phosphate using copper slag described in this embodiment comprises the following steps:
[0107] S1: Weigh 15g of copper slag in a corundum crucible and place it in a muffle furnace. Raise the temperature to 1000℃ at 10℃ / min, keep it at that temperature for 60min, and cool it to room temperature for later use. The XRD pattern of the calcined copper slag is as follows: Fig.13 As shown, compared with the original copper slag, the fayalite in the copper slag after roasting is completely decomposed, but the calcite solid solution phase appears, which is not conducive to the subsequent leaching and impurity removal.
[0108] S2: Take the copper slag from step S1, add 160 g / L NaOH solution at a liquid-to-solid ratio of 5:1, heat and stir, the leaching temperature is 110°C, the stirring rate is 130 rpm, the reaction time is 3 h, and after solid-liquid separation, a silicon-rich solution and alkaline leaching residue are obtained.
[0109] S3: Take the alkaline leaching residue from step S2, add 2M hydrochloric acid solution at a liquid-to-solid ratio of 12:1 and heat with stirring. The leaching temperature is 95°C, and the reaction is stirred at 150 rpm for 3 hours. Filter while hot to obtain an acid leaching solution and a filter residue.
[0110] S4: Add NaF to the acid leaching solution at 2.0 times the theoretical NaF mass of AlF3, MgF2, and CaF2 as the product, stir at 200 rpm for 1.5 hours at room temperature, separate the solid and liquid, and precipitate the purified liquid and impurities.
[0111] S5: Add diammonium hydrogen phosphate solution to the purified solution in step S4 at a stirring speed of 400 rpm with a P:Fe ratio of 1.25, and adjust the pH to 1.5. The reaction time is 1 hour, and then the temperature is raised to 90°C for aging for 5 hours. Immediately after the reaction, the solution is filtered and washed with hot water for 3 times. The filter residue is placed in a 100°C forced air drying oven for drying to obtain dihydrated iron phosphate.
[0112] S6: Sinter the dihydrate iron phosphate obtained in step S5 at 650° C. in an air atmosphere for 3 h, and grind to obtain anhydrous iron phosphate
[0113] S7: The anhydrous iron phosphate obtained in step S6 is mixed with the molar mass ratio of iron phosphate to lithium carbonate of 2:1, the amount of glucose added is 20% of the theoretical mass of lithium iron phosphate, and the mass ratio of zirconium oxide balls to the material is 10:1, and then anhydrous ethanol is added to submerge the balls, and the material is ground in a planetary ball mill for 4 hours at a speed of 700 rpm. Then the balls are separated and the mixture is dried at 70°C for 10 hours.
[0114] S8: The dry material obtained in step S7 is placed in a corundum crucible, and calcined in a tube furnace for 10 hours with nitrogen as protective gas, the calcination temperature is 700° C., and the air flow rate is controlled to be 300 ml / min. The element composition of the obtained lithium iron phosphate is shown in Table 3.
[0115] In summary, the present invention proposes a method for preparing lithium iron phosphate using copper slag. The oxidative roasting method of the present invention realizes the oxidative decomposition of ferrosilicate, can obtain a relatively ideal leaching efficiency, and is beneficial to the pH adjustment and precipitation of iron phosphate in the subsequent aging process. The alkaline leaching and purification process separate Si, Al, Ca, and Mg respectively, which is beneficial to the recycling of organic components. The leachate is finally synthesized into lithium iron phosphate positive electrode material, realizing the high-value utilization of copper slag.
[0116] The present invention is conducive to the preparation of lithium iron phosphate positive electrode materials with high discharge capacity, stable cycle performance and excellent rate performance, and provides a new idea for the preparation of lithium iron phosphate positive electrode material precursors.
[0117] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing lithium iron phosphate using copper slag, characterized in that: The following steps are involved: S1: roasting the copper slag in air atmosphere for 20-60 minutes; S2: Mix the calcined copper slag with sodium hydroxide solution and heat for 3 hours before solid-liquid separation; S3: adding hydrochloric acid solution to the alkali leaching residue, heating and stirring for a period of time, filtering while hot to obtain acid leaching solution and acid leaching residue; S4: Add Al to the acid leaching solution 3+ , Ca 2+ and Mg 2+ Add 1-2.5 times the theoretical mass of sodium fluoride to precipitate, and stir to react for 0.5-2.5h; After filtering, a purified acid extract and a filter residue are obtained, and the filter residue is dried and collected and stored; S5: adding diammonium hydrogen phosphate solution to the acid leaching solution, adjusting the pH under heating conditions, reacting for 1 hour, heating and aging, filtering, washing, and drying to obtain ferric phosphate dihydrate; S6: heating the obtained dihydrated ferric phosphate in air to dehydrate it, thereby obtaining anhydrous ferric phosphate; S7: after mixing anhydrous ferric phosphate, lithium carbonate and glucose, ball milling is performed for a period of time using ethanol as a dispersant, and then the slurry is dried and the ball material is separated; S8: After grinding the dry material, calcining it in an argon atmosphere to obtain a lithium iron phosphate positive electrode material. Furthermore, in step S1, the calcining temperature of the copper slag is 800-1000° C., and the calcining time is 20-60 min.
2. A method for preparing lithium iron phosphate using copper slag as claimed in claim 1, characterized in that: In step S1, the calcination temperature of the copper slag is 800-1000° C., and the calcination time is 20-60 min.
3. A method for preparing lithium iron phosphate using copper slag as claimed in claim 1, characterized in that: The process temperature in step S2 is 110° C., the stirring rate is 130 rpm, the concentration of the sodium hydroxide solution is 160 g / L, the reaction liquid-to-solid ratio is 5:1, and the reaction time is 3 h.
4. A method for preparing lithium iron phosphate using copper slag as claimed in claim 1, characterized in that: The process temperature in step S3 is 75-95° C., the stirring rate is 100-120 rpm, the concentration of the hydrochloric acid solution is 2 M, the reaction liquid-to-solid ratio is 8-12:1, and the reaction time is 1-3 h.
5. The method for preparing lithium iron phosphate using copper slag according to claim 1, characterized in that: The amount of sodium fluoride added in step S4 is 1-2.5 times the sum of the theoretical mass of sodium fluoride required for Al, Mg and Ca fluorides in the acid leaching solution, the stirring rate is 400 rpm, and the reaction time is 0.5-1.5 h.
6. A method for preparing lithium iron phosphate using copper slag as claimed in claim 1, characterized in that: In step S5, the amount of diammonium hydrogen phosphate added is calculated according to P:Fe=1.10-1.25, the reaction temperature is 65°C, the reaction time is 60 minutes, the aging temperature is 90°C, the aging time is 5 hours, the drying temperature is 80°C, and the drying time is 10 hours.
7. A method for preparing lithium iron phosphate using copper slag as claimed in claim 1, characterized in that: The heating time of step S6 is 3 hours, and the heating temperature is 650°C.
8. The method for preparing lithium iron phosphate using copper slag according to claim 1, characterized in that: The molar mass ratio of iron phosphate to lithium carbonate in step S7 is 2:1, the amount of glucose added is 20% of the theoretical mass of lithium iron phosphate, the mass ratio of zirconium oxide balls to material is 10:1, ethanol is added to submerge the ball material, the planetary ball mill speed is 700, the ball milling time is 4 hours, and the slurry drying temperature is 70°C.
9. The method for preparing lithium iron phosphate using copper slag according to claim 1, characterized in that: The sintering temperature of step S8 is 700° C., the sintering time is 10 h, and the argon gas flow rate is 300 ml / min.
Citation Information
Patent Citations
A method for preparing battery-grade ferric phosphate dihydrate using flotation copper tailings
CN117326538B
Method for preparing lithium iron phosphate from ferrophosphorus slag and application of lithium iron phosphate
CN118026136A
Short-process method for preparing iron phosphate from laterite-nickel ore and phosphorite
CN118479437A